A MOF@COF Composite with Enhanced Uptake through Interfacial Pore Generation. (3rd June 2019) - Garzón‐Tovar, Luis; Pérez‐Carvajal, Javier; Yazdi, Amirali; Hernández‐Muñoz, Jose; Tarazona, Pedro; Imaz, Inhar; Zamora, Félix; Maspoch, Daniel
Abstract: Herein, we describe a new class of porous composites comprising metal–organic framework (MOF) crystals confined in single spherical matrices made of packed covalent‐organic framework (COF) nanocrystals. These MOF@COF composites are synthesized through a two‐step method of spray‐drying and subsequent amorphous (imine‐based polymer)‐to‐crystalline (imine‐based COF) transformation. This transformation around the MOF crystals generates micro‐ and mesopores at the MOF/COF interface that provide far superior porosity compared to that of the constituent MOF and COF components added together. We report that water sorption in these new pores occurs within the same pressure window as in the COF pores. Our new MOF@COF composites, with their additional pores at the MOF/COF interface, should have implications for the development of new composites. Abstract : Grenzflächenporen : Eine neue Klasse von porösen Kompositmaterialien bestehend aus MOF‐Kristallen in sphärischen Matrizen aus gepackten COF‐Nanokristallen wird vorgestellt. Die MOF@COF‐Komposite besitzen Mikro‐ und Mesoporen an der MOF/COF‐Grenzfläche mit höherer Porosität als die Summe der MOFs und COFs.